The Impact of a Dementia-Friendly Exercise Class on People Living with Dementia: A Mixed-Methods Study - Long, Annabelle (Int J Environ Res Public Health, 2020)
Exercise has multiple benefits for people living with dementia. A programme of group exercise classes for people with dementia and their family carers has been established in a University sports centre. This study aims to explore the impact of this programme on participants with dementia and their carers. A mixed-methods design including a prospective, repeated measures cohort study followed by focus groups was employed. Physiological and cognitive outcome measures were repeated at baseline and three months in a cohort of people with dementia attending a group exercise class. Focus groups on the participants’ experiences and their perceptions of the impact of the exercise class on their lives were then conducted. The results were analysed and mapped on a model, to illustrate the components that most likely promote participation. Sixteen participants (n = 8 with dementia, and n = 8 carers) were recruited, and completed both baseline and follow up assessments. Positive mean differences were found in physical activity (4.44), loneliness (1.75), mood (1.33) and cognition (1.13). Ten participants were included in the focus groups, which found that accessibility of the exercise venue, opportunities for socialisation and staff who were experienced working with people living with dementia were key to participants reporting benefits. The four key themes from the focus group data were synthesised to produce a model outlining the components that might generate a positive impact of the exercise classes and promote participation. Exercise classes for people with dementia can be delivered with success in novel environments such as University sports centres. There is some indication of improvement over a short period of time. The model derived from this study will inform strategies to promote attendance at dementia-friendly exercise classes.